A case report of primary osteosarcoma originating from kidney. Issue 4 (January 2019) - Huang, Changkun; Zhu, Xuan; Xiong, Wei; Zhao, Xiaokun; Xu, Ran
Abstract: Rationale: Primary osteosarcoma of the kidney is a very rare subtype of renal neoplasms. There are only 27 cases reported in the literature since 1936. In addition, it has a high risk of metastasis and very low survival rate. Patient's concerns: In this report, we present a case of unique large osteosarcoma originated from the left kidney (21 cm × 18 cm × 11 cm) with lung metastasis. A 48-year-old female patient presented with intermittent abdominal distension and gross hematuria. Diagnoses: A computed tomography scan of the abdomen confirmed a large solid, partly calcified mass in the left retroperitoneum, with lung metastasis (IV stage according to AJCC). The radical nephrectomy was performed. The postoperation immunohistochemical analysis supporting the diagnosis of osteosarcoma. Interventions: The patient received chemotherapy with ifosfamide, cisplatinum, pirarubicin and then target therapy with anlotinib (12 mg per day, per os; days 1–14; 21 days per cycle) after surgery. Outcomes: The patient was followed up for 26 months, with no postoperative complications, no tumor recurrence, and no progress in pulmonary metastasis. Lessons: The case reported here is a unique large osteosarcoma originated from the kidney (21 cm × 18 cm × 11 cm) at an advanced stage (IV). However, the patient's condition was controlled for at least 26 months after surgical resection and postoperative chemotherapy, which had never been reported in the literature before. Additionally, 3 mutated genes were found in the tissue by genetic testing, which we suspect that is the reason why this patient is sensitive to chemotherapy and thus has longer survival.